2004
DOI: 10.1037/0735-7036.118.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Object Permanence in Common Marmosets (Callithrix jacchus).

Abstract: A series of 9 search tasks corresponding to the Piagetian Stages 3-6 of object permanence were administered to 11 common marmosets (Callithrix jacchus). Success rates varied strongly among tasks and marmosets, but the performances of most subjects were above chance level on the majority of tasks of visible and invisible displacements. Although up to 24 trials were administered in the tests, subjects did not improve their performance across trials. Errors were due to preferences for specific locations or boxes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…de Blois & Novak, 1994;de Blois et al, 1998;Deppe et al, 2009;Fedor et al, 2008;Mendes & Huber, 2004;Neiworth et al, 2003]. We also analyzed all the trials in the sequential visible task in the present study, for comparison with past research.…”
Section: Visible Displacementsmentioning
confidence: 98%
See 1 more Smart Citation
“…de Blois & Novak, 1994;de Blois et al, 1998;Deppe et al, 2009;Fedor et al, 2008;Mendes & Huber, 2004;Neiworth et al, 2003]. We also analyzed all the trials in the sequential visible task in the present study, for comparison with past research.…”
Section: Visible Displacementsmentioning
confidence: 98%
“…Gibbons and marmosets have been tested on invisible displacement controls [Fedor et al, 2008;Mendes & Huber, 2004]; however, small sample sizes and high individual variability in performance makes it difficult to come to firm conclusions about these species' understanding of invisible displacements. Recent studies on domestic dogs have indicated that this species cannot solve rigorously controlled invisible displacements [Collier-Baker et al, 2004;Fiset & LeBlanc, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…However, in a computerized task, rhesus macaques could predict the path of an occluded object, suggesting that they could represent unperceived object movements (Fillion, Washburn, & Gullege, 1996). In a recent study (Mendes & Huber, 2004), 2 out of 11 common marmosets (Callithrix jacchus) achieved very high scores in successive invisible displacement tasks, suggesting that this species is also able to represent the existence and the movements of invisible objects. Neiworth et al (2003) claimed that cotton top tamarins (Saguinus oedipus) also reach Stage 6 of object permanence; however, their methodology was unusual in that they opened the displacement device between the two boxes of all double invisible displacements.…”
Section: Object Permanence In Great Apes and Monkeysmentioning
confidence: 99%
“…Studies have also begun to reveal how other species represent objects (e.g., Pepperberg and Kozak 1986;Goulet et al 1994;Funk 1996;Pepperberg et al 1997;Pollock et al 2000;Cooper et al 2003;Fiset et al 2003Collier-Baker et al 2004;Mendes and Huber 2004;Fiset and Doré 2006;Zucca et al 2007;Miklósi 2007;Miller et al 2009;Whitt et al 2009;Deppe et al 2009). Indeed, such explorations could provide new insights into tasks with human and non-human primate populations.…”
Section: Introductionmentioning
confidence: 99%